Ag nanoparticles anchored on oxygen vacancy-rich alumina catalyst for efficient bacterial inactivation - Ting Wang; Fangyuan Gu; Leyang Xu; Wenqi Tang; Yanfeng Han; Yongjie Wang; Shi Yang; Weiying Wang; Xinlong Zhang; Tianshuo Zhao; Biao Ran; Chaopeng Fu; et al. (Chemical Engineering Journal, 2025)

Bifunctional hyperbranched modifier enabled interlocking interfaces for ultra-strong recyclable carbon fiber/bio-epoxy composites - Dan Li; Shucun Zhou; Yu Wu; Tianshuo Li; Tingcheng Li; Hao Li; Zejun Xu; Sufang Chen; Yu Jiang; Daohong Zhang (Chemical Engineering Journal, 2025)

Axial mechanical response of concrete pipe jacking considering the deflection of the bell-and-spigot joint: Full-scale test and numerical simulation - Kaixin Liu; Xiaolong Chen; Peng Zhang; Baosong Ma; Xin Feng; Yunlong Zhang; Hao Liu; Xuhong Tan; Tianshuo Xu (Tunnelling and Underground Space Technology, 2024)

Mechanical response of diaphragm wall supporting deep launch shaft induced by braced excavation and pipe jacking operation - Kaixin Liu; Samuel T. Ariaratnam; Peng Zhang; Xiaolong Chen; Jing Wang; Baosong Ma; Yunlong Zhang; Xin Feng; Tianshuo Xu (Tunnelling and Underground Space Technology, 2023)

Field mechanical properties of large section concrete pipes during jacking in fractured moderately weathered siltstone - Xin Feng; Peng Zhang; Xiaolong Chen; Yunlong Zhang; Baosong Ma; Kaixin Liu; Tianshuo Xu; Cong Zeng (Tunnelling and Underground Space Technology, 2023)

Changes in water color shift competition between phytoplankton species with contrasting light‐harvesting strategies - Veerle M. Luimstra; Jolanda M. H. Verspagen; Tianshuo Xu; J. Merijn Schuurmans; Jef Huisman (Ecology, 2020)
The color of many lakes and seas is changing, which is likely to affect the species composition of freshwater and marine phytoplankton communities. For example, cyanobacteria with phycobilisomes as light‐harvesting antennae can effectively utilize green or orange‐red light. However, recent studies show that they use blue light much less efficiently than phytoplankton species with chlorophyll‐based light‐harvesting complexes, even though both phytoplankton groups may absorb blue light to a similar extent. Can we advance ecological theory to predict how these differences in light‐harvesting strategy affect competition between phytoplankton species? Here, we develop a new resource competition model in which the absorption and utilization efficiency of different colors of light are varied independently. The model was parameterized using monoculture experiments with a freshwater cyanobacterium and green alga, as representatives of phytoplankton with phycobilisome‐based vs. chlorophyll‐based light‐harvesting antennae. The parameterized model was subsequently tested in a series of competition experiments. In agreement with the model predictions, the green alga won the competition in blue light whereas the cyanobacterium won in red light, irrespective of the initial relative abundances of the species. These results are in line with observed changes in phytoplankton community structure in response to lake brownification. Similarly, in marine waters, the model predicts dominance of Prochlorococcus with chlorophyll‐based light‐harvesting complexes in blue light but dominance of Synechococcus with phycobilisomes in green light, with a broad range of coexistence in between. These predictions agree well with the known biogeographical distributions of these two highly abundant marine taxa. Our results offer a novel trait‐based approach to understand and predict competition between phytoplankton species with different photosynthetic pigments and light‐harvesting strategies.